Decision-making at technological systems structure upgrade - Мелкумян, В.Г. (Proceedings of National Aviation University (archive), 2004)
The method based on use of expert ratings of variants of upgrade of structure of technological system with result application of the theory of fuzzy sets is considered. The suggested way of a choice of optimum decisions from alternative variants of structure of technological systems under unsympathetic target conditions, will allow to minimize economic and social consequences of its upgrade. Results of research can be used at the initial stages of complex technical systems designing at insufficient volume on absence of the necessary statistical data.